Intracranial and Extracranial Vertebrobasilar Artery Stenosis Patient Profile in Dr. Moewardi General Hospital - Subandi, Subandi; Suroto, Suroto; Mirawati, Diah Kurnia; Danuaji, Rivan; Budianto, Pepi; Hambarsari, Yetty; Hamidi, Baarid Luqman; Prabaningtyas, Hanindia Riani; Hutabarat, Ervina Arta Jayanti; Tejomukti, Teddy; Ristinawati, Ira; Tedjo, Raden Andi Ario; Pretikasari, Zefania Yonisa; Hafizhan, Muhammad; Putra, Stefanus Erdana (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: Vertebrobasilar artery stenosis can be extracranial or intracranial, and accounts for up to 20% of posterior circulation ischemic strokes. The gold standard for diagnosing is Digital Subtraction Angiography (DSA), an invasive diagnostic method by injecting a contrast agent into the blood vessels leading to the brain through a catheter. This study aims to determine the profile of patients with intracranial and extracranial vertebrobasilar artery stenosis who underwent DSA procedures.Methods: This descriptive research was conducted in RSUD Dr. Moewardi in patients who underwent DSA procedures for the period January 2020 to March 2022 and found vertebrobasilar artery stenosis. The study samples were grouped based on the location of the stenosis; intracranial and extracranial. The data collected included age, gender, symptoms, risk factors, degree of stenosis, and angiographic findings.Results: Of 42 subjects, 33 (78.6%) patients were male. There are 23 (54.8%) patients with intracranial vertebrobasilar stenosis and 19 (45.2%) patients in extracranial. The main symptoms included hemiparesis, vertigo, hemiesthesia, loss of consiciousness, aphasia, dysartria, and dysphagia. The risk factors were 36 (85.7%) patients with hypertension, 18 (42.9%) patients with diabetes mellitus, 18 (42.9%) patients with a history of smoking, and 13 (31%) patients with hyperlipidemia. A total of 8 patients underwent stenting/angioplasty.Conclusion: The prevalence of vertebrobasilar artery stenosis increases with age, most commonly occurring at the age of 50-59 years..The most common risk factor for vertebrobasilar artery stenosis is hypertension. Management recommendations include a combination of antiplatelet and endovascular therapy.